Systematic serials selection analysis in a small academic health sciences library. - Byrd, G D (1978)
This paper describes the implementation of a straightforward quantitative technique to analyze the serials collection of the Medical Library at the University of Missouri-Kansas City (UMKC). Our simplified operations research approach resulted in a savings of nearly $1400 per year in subscriptions costs without reducing the net number of seven hundred titles or causing an imbalance in the subject distribution of our collection. By detailing both the rationale behind the process and the actual steps followed at UMKC, we hope to demonstrate that operations research techniques can be used practically and successfully even in small health sciences libraries. In the Appendix a more general and more rigorous operations research approach to the analysis of serials collections is also presented in a fashion that is, as far as possible, not mathematically forbidding.